2021
DOI: 10.1002/csc2.20473
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression gene network analysis of cold‐tolerant Solanum commersonii reveals new insights in response to low temperatures

Abstract: Among abiotic stressors, cold is one of the most harmful for the cultivated potato (Solanum tuberosum L.), a frost-sensitive crop. RNA sequencing (RNA-seq) profiling of two different clones of wild potato (S. commersonii Dun.) contrasting in their capacity to withstand low temperatures revealed a higher number of differentially expressed genes (DEGs) under nonacclimated conditions (NAC) in tolerant clone cmm1T vs. the susceptible cmm6-6 (1,002 and 8,055 DEGs, respectively). By contrast, the number of DEGs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Weighted gene co-expression network analysis (WGCNA) is widely used in key gene or module screening (Esposito et al, 2021;Zhu et al, 2019). By this method, the DEmRNAs and DElncRNAs were further narrowed to modules highly-related to CGA content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weighted gene co-expression network analysis (WGCNA) is widely used in key gene or module screening (Esposito et al, 2021;Zhu et al, 2019). By this method, the DEmRNAs and DElncRNAs were further narrowed to modules highly-related to CGA content.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting important genes or pathways from a large number of DEGs is a large challenge in transcriptomics analysis. Weighted gene co‐expression network analysis (WGCNA) is widely used in key gene or module screening (Esposito et al, 2021; Zhu et al, 2019). By this method, the DEmRNAs and DElncRNAs were further narrowed to modules highly‐related to CGA content.…”
Section: Discussionmentioning
confidence: 99%
“…After the preliminary module division, the modules with similar expression patterns were combined according to the module similarity to form a dynamic tree. Subsequent analyses were carried out according to the combined module ( Esposito et al, 2021 ). The KEGG pathway enrichment analysis was performed using the KEGG database ( http://www.genome.jp/kegg/ ) ( Minoru et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has found that WGCNA is more sensitive to noise in datasets and outperforms other clustering methods in detecting non-overlapping clusters or modules [39]. The WGCNA has been reported in several publications related to crop improvement [40][41][42][43][44].…”
Section: Command-line Tools 221 Weighted Correlation Network Analysis...mentioning
confidence: 97%